Chemical constituents from the leaves of Tripterygium wilfordii and their cytotoxic activity. Issue 1 (January 2022) - Jiang, Zhi-Chao; Li, Zi-Heng; Li, Peng-Yu
A new flavonol glycoside derivate named kaempferol 3- O - trans - p -coumaroyl-7- O - α -ʟ-rhamnoside (1 ), together with five known compounds (2–6 ), was isolated from the EtOAc-soluble extract of the leaves of Tripterygium wilfordii . The structure of new compound was elucidated with spectroscopic and physico-chemical analyses. All the isolates were evaluated for in vitro cytotoxic activity against four human cancer cells including HepG2, Hep3B, A549 and MCF-7. Among them, compound1 exhibited the significant cytotoxic activities against HepG2 and Hep3B cells with IC50 values of 6.8 ± 1.6 and 4.2 ± 1.3 μM, respectively. The above data demonstrated the potential of1 for the treatment of liver cancer. In addition, 4 also showed moderate inhibitory activity on HepG2 and Hep3B cells with IC50 values of 16.1 ± 2.3 and 10.7 ± 1.8 μM, respectively.